(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to identify conceptual harmony in art and its relationship to the artistic style of art education students. The research community consisted of (10) artworks, and (3) artworks were selected as a sample for analysis. A descriptive approach (content analysis) was used because it suited the research objective. A research tool was created consisting of an analysis form. Statistical methods were used, including the Cooper equation to determine the percentage of agreement, the Scott equation to calculate the validity of the tool, and the Pearson correlation coefficient to extract reliability using the split-half method. The most important results: Conceptual harmony was achieved through the color and linear harmony of the form in the artistic output. The Student Artist found in free formal systems ample scope for exploring meanings that are not defined by specific elements and their relationship to the artistic style. The most important conclusions: Conceptual harmony leads to our understanding of the symbols, rules, and connotations present in the visual image, which leads to the possibility of reading it and understanding its artistic relationships.